Kesadaran Hukum Masyarakat terhadap Privasi Digital: Potret, Faktor Determinan, dan Tantangan dalam Mewujudkan Kepatuhan terhadap UU PDP - Gilang Rizki Aji Putra (UIN Jakarta, 2022)
This article analyzes public legal awareness of digital privacy in Indonesia and its implications for implementing Law No. 27/2022 on Personal Data Protection (PDP Law). Using normative-sociological legal research and secondary data from digital literacy surveys, the study finds that public awareness remains superficial and is not consistently reflected in protective behavior. Low digital literacy, power imbalances between individuals and corporations, and cultural perceptions of privacy as a secondary value contribute to this condition. Major data breach cases reveal a gap between knowledge and action. The article recommends strengthening digital privacy education, literacy campaigns, and accessible complaint mechanisms. Keywords: Legal Awareness, Digital Privacy, PDP Law, Digital Literacy, Legal Culture.